TEMPERATURE, LIGHT, AND DESICCATION TOLERANCE IN SEED GERMINATION OF Mauritia flexuosa L.F. - Almeida,Lívia Caroline Praseres de (2018)
ABSTRACT Palm trees are widely used as ornamental plants, besides its sustainability and industry aspects. These plants are commercially propagated via seeds. Due to its importance and the need for seed germination information, this study aimed to verify the effect of temperature, light regimes, and desiccation tolerance on germination of Mauritia flexuosa L.f. For that, two completely randomized experiments were carried out. The first consisted of treatments arranged in a 6 x 2 factorial scheme, testing six temperatures (20, 25, 30, 35, 20-30, and 25-35 ºC) and light presence and absence. The second comprised five seed water contents (51, 48, 45, 30, and 26%) for desiccation tolerance evaluations. Water content measurements were made every three days, from a sample lot maintained at room temperature. In both trials, each treatment was composed of four replicates with 25 seeds per plot. Germination rate (GR) and germination speed index (GSI) were calculated, and the data were analyzed by analysis of variance (ANOVA). Temperature and light means were compared by the Tukey’s test (p < 0.05), and the desiccation ones by a polynomial regression. The highest GR was observed at 20-30 ºC, regardless of light presence. Moreover, M. flexuosa seeds were sensitive to desiccation.